Inculcating National Values for Students' Character Building of the Faculty of Social and Political Sciences Sangga Buana University through Campus Extracurricular Program - H. Muchsin al-Fikri; Yuyun Yuniarsih; Tresia Wulandari (Universitas Sebelas Maret, 2021)
Students are a generation full of potential and achievements. Education at the University should encourage them to develop their hidden potential to become the successor and continuation of national development. Unfortunately, the cultivation of national values is still limited to transfer of knowledge and has not yet reached the transfer of value. Each student has a unique potential that can be developed according to their background and characteristics. There are those who have the potential to become leaders, there are also those who tend to be adaptable and good at establishing interpersonal relationships with other people. But not a few also have temperamental. So it is not uncommon for them to be radical and rebellious. This is where the importance of cultivating the value of nationality so that his critical power is channeled to defend and love his country. This research discusses the program of inculcating national values for the formation of student character carried out by the Faculty of Social and Political Sciences at Sangga Buana University through extra-curricular activities. This research is a descriptive qualitative research with a case study approach.